2017
DOI: 10.3390/su9122283
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Water Use and Water Scarcity Footprint for Sustainable Rice Cultivation

Abstract: Rice cultivation is a vital economic sector of many countries in Asia, including Thailand, with the well-being of people relying significantly on selling rice commodities. Water-intensive rice cultivation is facing the challenge of water scarcity. The study assessed the volumetric freshwater use and water scarcity footprint of the major and second rice cultivation systems in the Chao Phraya, Tha Chin, Mun, and Chi watersheds of Thailand. The results revealed that a wide range of freshwater use, i.e., 0.9-3.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 24 publications
0
18
2
Order By: Relevance
“…In the LCA approach, the irrigation water used to produce a specific product and the water stress index (WSI) of the watershed from where the irrigation water is withdrawn are used to assess the water use impact i.e. deprivation potential (Silalertruksa et al, 2017;Pfister et al, 2009). WSI is the ratio of the freshwater withdrawal on an annual basis to its availability within the basin (Pfister et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LCA approach, the irrigation water used to produce a specific product and the water stress index (WSI) of the watershed from where the irrigation water is withdrawn are used to assess the water use impact i.e. deprivation potential (Silalertruksa et al, 2017;Pfister et al, 2009). WSI is the ratio of the freshwater withdrawal on an annual basis to its availability within the basin (Pfister et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The deprivation potential of water is an important tool to assess the water use impacts on human beings and ecosystems. The related water use impact is less with a lower value of water scarcity footprint and vice versa (Silalertruksa et al, 2017;Gheewala et al, 2017). The deprivation potential of water can be determined by using the Equation 6.…”
Section: Methodsmentioning
confidence: 99%
“…The water supplies of the rice field are from two sources, i.e., rainwater and irrigation water. According to a study by [12], in the Chao-praya river region, the rice yield of 1 kg requires the amount of rainwater and irrigation water for 1.08 liter and 0.35 liter respectively.…”
Section: Agricultural Usementioning
confidence: 99%
“…To accurately quantify the water consumption, the life cycle analysis (LCA) is used to analyze the water consumption related to each activity of the life cycle. Since the main water supply of rice is from two sources, rainwater and irrigation water, according to Silalertruksa et al [13], the relationship between rice yield and water use is shown in Table 1.…”
Section: Life Cycle Analysismentioning
confidence: 99%